2015
DOI: 10.1107/s1399004714024869
|View full text |Cite
|
Sign up to set email alerts
|

The design and structural characterization of a synthetic pentatricopeptide repeat protein

Abstract: Proteins of the pentatricopeptide repeat (PPR) superfamily are characterized by tandem arrays of a degenerate 35-amino-acid α-hairpin motif. PPR proteins are typically single-stranded RNA-binding proteins with essential roles in organelle biogenesis, RNA editing and mRNA maturation. A modular, predictable code for sequence-specific binding of RNA by PPR proteins has recently been revealed, which opens the door to the de novo design of bespoke proteins with specific RNA targets, with widespread biotechnological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 60 publications
5
60
0
Order By: Relevance
“…Similar to PUF proteins, several PPR proteins have been successfully modified to recognize corresponding RNA targets through simply modifying the critical amino acids of each PPR motif (9,(12)(13)(14)(15)(16)(17). Considering the PPR motifs have been designed to target a specific transcript, if RNA endonuclease activity can be confirmed for the SMR domain of PPR-SMR proteins, the PPR-SMR protein will enable "engineering" of sequence-specific RNA endonucleases, which will have exciting applications for RNA manipulation (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to PUF proteins, several PPR proteins have been successfully modified to recognize corresponding RNA targets through simply modifying the critical amino acids of each PPR motif (9,(12)(13)(14)(15)(16)(17). Considering the PPR motifs have been designed to target a specific transcript, if RNA endonuclease activity can be confirmed for the SMR domain of PPR-SMR proteins, the PPR-SMR protein will enable "engineering" of sequence-specific RNA endonucleases, which will have exciting applications for RNA manipulation (27).…”
Section: Discussionmentioning
confidence: 99%
“…The 2nd, 5th, and 35th (or 1st, 4th, and 34th or 3rd, 6th, and 1st in other numbering systems) residues at each repeat are considered to be RNA selection "codes" (9-11). Based on these codes, several PPR proteins have been successfully modified to recognize predictable RNA targets (9,(12)(13)(14)(15)(16)(17).The small MutS-related (SMR) domain was originally identified at the C terminus of MutS2 in the cyanobacterium Synechocystis (18). SMR proteins are widely distributed in almost all organisms (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…P-type PPR proteins were shown to participate in various aspects of organellar RNA processing, whereas PLS PPR proteins have been almost exclusively associated with C-to-U RNA editing (for review, see Barkan and Small, 2014;Hammani and Giegé, 2014). Recent crystal structures showed that PPR motifs adopt an antiparallel helixturn-helix fold whose repetition forms a solenoid-like structure (Ringel et al, 2011;Howard et al, 2012;Ban et al, 2013;Yin et al, 2013;Coquille et al, 2014;Gully et al, 2015). PPR tracks organize highly specific interaction domains that were shown to associate with single-stranded RNAs (Schmitz-Linneweber et al, 2005;Beick et al, 2008;Uyttewaal et al, 2008a;WilliamsCarrier et al, 2008;Pfalz et al, 2009;Cai et al, 2011;Hammani et al, 2011;Prikryl et al, 2011;Khrouchtchova et al, 2012;Manavski et al, 2012;Zhelyazkova et al, 2012;Ke et al, 2013;Yin et al, 2013).…”
mentioning
confidence: 99%
“…Multiple copies of the unit are then linked to create a homogeneous repeat protein sequence; capping repeats are derived from naturally existing proteins. Consensus design has been the first and most widely used approach across multiple repeat protein families: ankyrin (ANK) [9][10][11][12][13], tetratricopeptide repeat (TPR) [14], armadillo (ARM) [15][16][17], leucine rich repeat (LRR) [18], pentatricopeptide repeat (PPR) [19,20], pentapeptide repeat [21], 42 residue TPR variant (42PR) [22] and HEAT-EZ [23], all have designed structures confirmed by crystallography (Table 1). Effective consensus design relies on the assumption that evolutionary conservation translates into self-compatibility of repeats and foldability of the structures.…”
Section: Introductionmentioning
confidence: 99%